2019
DOI: 10.1186/s10195-019-0519-1
|View full text |Cite
|
Sign up to set email alerts
|

Tibia plateau fracture mapping and its influence on fracture fixation

Abstract: Background Tibial plateau fracture classifications are based on anteroposterior radiographs. Precontoured locking plates are commonly used to treat such fractures. The aims of this study are to: (1) describe tibial plateau fracture anatomy in the axial plane and (2) assess whether current plating systems allow screws to be placed suitably. Materials and methods A graphical tibial plateau template was developed. One hundred twenty-five tibial plateau fractures (four bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 17 publications
0
38
0
2
Order By: Relevance
“…Fracture mapping can record the size, shapes, numbers, and orientations of fracture fragments, and help surgeons determine the optimal treatment (5). To date, fracture mapping has been applied to scapular, tibial, hip, and acetabular fractures (6)(7)(8)(9)(10)(11). However, there have been no reports concerning fracture mapping for the treatment of calcaneal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Fracture mapping can record the size, shapes, numbers, and orientations of fracture fragments, and help surgeons determine the optimal treatment (5). To date, fracture mapping has been applied to scapular, tibial, hip, and acetabular fractures (6)(7)(8)(9)(10)(11). However, there have been no reports concerning fracture mapping for the treatment of calcaneal fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The usefulness of fracture mapping has undoubtedly contributed to the understanding and treatment of mapped fractures, including the tibia plateau (6), olecranon (7) and scapula (8). An improved understanding of fracture morphology, based on computed tomography (CT) and quantitative 3-dimensional CT (3D CT) analysis of the clavicle, might guide decision-making and implant development.…”
Section: Introductionmentioning
confidence: 99%
“…However, the treatment of bicondylar TPFs remains controversial. Many scholars have suggested that isolated lateral locking plates, dual plating and additional posterior buttress plating can all be used to treat bicondylar TPFs 6 , 9 , 18 , 19 . At present, although lateral locking plates are widely used in bicondylar TPFs, an additional medial support plate is often required when the fragments of the medial condyle are small, comminuted, osteoporotic, or have coronal fractures 7 , 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%